The five cat club - Makris, Kathryn (New York : Avon, 1994)
Before Cary, Sienna and Jess manage to find homes for five homeless kittens, they discover that their pets are just one small part of a much larger problem.
5.7
5-8
5-8
Keywords: Cats -- Fiction; Cats -- Fiction